SIMULATION PROCEDURE OF ORIGINAL-DESTINATION MATRIX BASED ON SAMPLE SURVEY RESULTS BY CARD METHOD - Horbachov, P.; Rossolov, A.; Honcharenko, S.; Горбачёв, П. Ф.; Россолов, А. В.; Гончаренко, С. Ю.; Горбачов, П. Ф.; Россолов, О. В. (Харьковский национальный автомобильно-дорожный университет, 2015)
A new method for forming the matrix of passenger correspondences based on the results of field investigations on the route network is developed. The procedure of determining the matrix of network correspondences presupposes the implementation of 3 stages that the appropriate parameters of demand for transportation are based on each of them. The key aspect of the method developed is considerable reduction of labour-effectiveness of carrying out inspections on condition of preserving sufficient appropriateness of the data of the common massif.
МЕТОДИКА МОДЕЛИРОВАНИЯ МАТРИЦЫ СЕТЕВЫХ КОРРЕСПОНДЕНЦИЙ НА ОСНОВЕ РЕЗУЛЬТАТОВ ВЫБОРОЧНОГО ОБСЛЕДОВАНИЯ ТАБЛИЧНЫМ МЕТОДОМ
МЕТОДИКА МОДЕЛЮВАННЯ МАТРИЦІ МЕРЕЖНИХ КОРЕСПОНДЕНЦІЙ НА ОСНОВІ РЕЗУЛЬТАТІВ ВИБІРКОВОГО ОБСТЕЖЕННЯ ТАБЛИЧНИМ МЕТОДОМ
Keywords: trip; original-destination matrix; bus stop capacity; route network; пассажирская корреспонденция; матрица корреспонденций; емкость остановочного пункта; маршрутная сеть; пасажирська кореспонденція; матриця кореспонденцій; місткість зупинного пункту; маршрутна мережа; 656.025